PERTANGGUNG JAWABAN PIDANA TERHADAP FREELANCE PERUSAHAAN PADA TINDAK PIDANA PERBANKAN DALAM MENGHIMPUN DANA MASYARAKAT TANPA IZINOTORITAS JASA KEUANGAN ATAU BANK INDONESIA DENGAN PROMISSORY NOTE - Afrido Hidayah; Mukhlis R; Syaifullah Yophie Ardiyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
We can find arrangements regarding the accountability of the Board of Directors inLaw Number 40 of 2007 concerning Limited Liability Companies. Pursuant to Article 97paragraph (2) of the Limited Liability Company Law, the directors are required to managethe company in good faith and with full responsibility. Meanwhile, freelancers, who in factare only freelance daily workers and do not have a fixed monthly salary, are demandedalmost the same as the directors. So the purpose of the thesis research is first, to find outwhether a company can raise funds through a Promissory Note. Second, knowing whether afreelance can be held criminally responsible in a company, if the company commits a crime.This type of researcher can be classified into the type of normative legal research.This study uses secondary data consisting of primary legal materials, secondary legalmaterials, tertiary legal materials and data collection techniques are carried out using thelibrary method.From the results of the research problem there are two main things that can beconcluded. First, that in collecting public funds, the company can do this with a promissorynote (promissory note), based on Article 174 of the Criminal Code, it must meet therequirements. Second, that freelance companies cannot be held accountable for companiesthat commit criminal acts. If asked for accountability, it is only administrative. Because afreelance company is not included in the core organs of the company and is not included assomeone who can control the company in accordance with the Limited Liability CompanyLaw and the Criminal Code. The author's suggestion is First, the collection of public fundscarried out by non-bank companies is given more attention to the State of Indonesia.Enforcement and supervision must be carried out even tighter so that the Banking Act LawNumber 7 of 1992 concerning Banking and Law Number 21 of 2011 concerning theFinancial Services Authority is more effectively implemented so that people are no longerafraid to invest in shares to advance the economy. Second, if company freelancers are heldcriminally liable, then all freelance companies must also be held accountable in accordancewith the law regulated in article 2 of the Criminal Code.Keywords: Freelance, Financial Services Authority, Bank Indonesia.